STUDI TENTANG NILAI-NILAI PANCASILA YANG TERKANDUNG DALAM KEBUDAYAAN BARONGSAI DI BAGANSIAPIAPI KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Indah santia; Hambali '; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research background Pancasila as the outlook of the nation of Indonesia, Pancasila because in essence is not only a result of contemplation thinking person or group of persons as the ideologies that exist in the world such as markism and liberalism. However Pancasila values extracted from the customs, cultural values and religious values contained in the people’s lives Indonesian nation. As with Lionese culture That is done by 'the Chinese community OR Ethnic Chinese in Bagansiapiapi Which is A Tradition That done Operates Continuously From genersi To the next generation, formulation of the problem ON Research singer is whether contained Values Pancasila hearts Lionese Culture Chinese Society In Bagansiapiapi Rokan Hilir. The purpose of Research Singer is to review determine values of Pancasila Contained hearts Fuel Barge Traditional Chinese Society In Bagansiapiapi. Population Research hearts singer is whole Chinese society in Bagansiapiapi. While the technique of sampling purposive sampling technique Use That is as much as 30 people Of The Chinese Society Understanding And had about Criteria The lionese culture in Bagansiapaiapi. Data collection techniques which are used hearts Singer Research That use traditional questionnaires, interviews and document well as. Data analysis techniques used a hearts Singer That descriptive quantitative research with using the formula P = F / n x 100%. From the findings of research can be concluded that of the 30 respondents who stated Ya is 93,81%, that are values of Pancasila hearts Tradition fuel barge 'community tionghoa, and the declared NOT is 5,74% means that There are Values pancasia tradition hearts fuel barge 'community tionghoa and the declared not Answering 0.46%. So hearts Singer Research Proven Fuel Barge That tradition of Chinese Society Bangko Bagansiapiapi District of Rokan Hilir containing values of Pancasila.Keywords: Values Pancasila, Lionese culture Chinese Society.